Deletion of Topoisomerase 1 in excitatory neurons causes genomic instability and early onset neurodegeneration - Giulia Fragola (Nature Portfolio, 2020)
Topoisomerase 1 (TOP1) relieves DNA torsional stress during transcription and facilitates the expression of long neuronal genes. Here we show that deletion of Top1 in excitatory neurons leads to early onset neurodegeneration that is partially dependent on p53/PARP1 activation and NAD+ depletion.